Barriers to participation in classical music events by young Czechs - Tamášiová, Laura (2024)
Barriers to participation in classical music events by young Czechs. The thesis aims to delve into the factors influencing young Czechs (aged 18-24) in their participation in classical music events. It seeks to uncover both the barriers preventing their engagement and the motivating factors driving their attendance. Additionally, the research will explore the attitudes and motivations of these individuals concerning classical music and music in general. Lastly, the study will investigate the musical preferences of young Czechs. This thesis highlights three distinct dimensions of the research: 1. Barriers and Motivating Factors in Classical Music Engagement: This dimension of the research focuses on uncovering the obstacles that deter young Czechs (aged 18-24) from participating in classical music events. It will delve into issues such as ticket costs, accessibility, lack of awareness, or perceptions of exclusivity specific to classical music. Simultaneously, it seeks to identify the motivating factors that drive young individuals to attend classical music events. These motivations could include personal interest, educational experiences, cultural significance, or social influences unique to classical music. 2. Attitudes and Motivations Towards Classical Music and Music in General: This dimension explores the broader attitudes and motivations of young Czechs concerning classical music specifically. It examines their perceptions of classical music's relevance, its role in society, and any preconceived notions about its complexity or accessibility. Additionally, it investigates their general attitudes and motivations towards music as a whole, encompassing various genres and forms of musical expression. This allows for a comparison between classical music and other genres, revealing unique insights into their preferences. 3.